QCR7 affects the virulence of Candida albicans and the uptake of multiple carbon sources present in different host niches - Zeng, Lingbing; Huang, Yongcheng; Tan, Junjun; Peng, Jun; Hu, Niya; Liu, Qiong; Cao, YanLi; Zhang, Yuping; Chen, Junzhu; Huang, Xiaotian (Frontiers in Cellular and Infection Microbiology, 2023)
Background Candida albicans is a commensal yeast that may cause life-threatening infections. Studies have shown that the cytochrome b-c1 complex subunit 7 gene (QCR7) of C. albicans encodes a protein that forms a component of the mitochondrial electron transport chain complex III, making it an important target for studying the virulence of this yeast. However, to the best of our knowledge, the functions of QCR7 have not yet been characterized. Methods A QCR7 knockout strain was constructed using SN152, and BALb/c mice were used as model animals to determine the role of QCR7 in the virulence of C. albicans. Subsequently, the effects of QCR7 on mitochondrial functions and use of carbon sources were investigated. Next, its mutant biofilm formation and hyphal growth maintenance were compared with those of the wild type. Furthermore, the transcriptome of the qcr7Δ/Δ mutant was compared with that of the WT strain to explore pathogenic mechanisms. Results Defective QCR7 reduced recruitment of inflammatory cells and attenuated the virulence of C. albicans infection in vivo. Furthermore, the mutant influenced the use of multiple alternative carbon sources that exist in several host niches (GlcNAc, lactic acid, and amino acid, etc.). Moreover, it led to mitochondrial dysfunction. Furthermore, the QCR7 knockout strain showed defects in biofilm formation or the maintenance of filamentous growth. The overexpression of cell-surface-associated genes (HWP1, YWP1, XOG1, and SAP6) can restore defective virulence phenotypes and the carbon-source utilization of qcr7Δ/Δ. Conclusion This study provides new insights into the mitochondria-based metabolism of C. albicans, accounting for its virulence and the use of variable carbon sources that promote C. albicans to colonize host niches.